The Theory of the Use of Cloud Technologies in the Implementation of Hierarchical Preparation of Engineers - Ergashev Nuriddin G‘ayratovich (Genius Journals, 2022)
The article analyzes the importance of using bilutleie technologies in the implementation of hierarchical preparation of Engineers. It has been studied that cloud technology in education can provide access to a wider range of forms and methods of teaching, as well as one of the modern methods of intensification and optimization of the learning process.
Keywords: Cloud Technology; Education System; New Educational Technology